The Impact of Work Attitude on Job Satisfaction and Intention to Change Jobs on the Fashion Model Industry in Jakarta - Theressa, Stevanny Putri; Baihaqi, Imam (International Journal of Business and Management Technology in Society, 2026)
Purpose – This study aims to investigate the impact of work attitude on job satisfaction and the intention to change jobs within the fashion modeling industry in Jakarta. The focus is on freelance fashion models who often face job insecurity and a lack of legal protection. Methodology – A quantitative approach was employed using confirmatory factor analysis. Data were collected through a questionnaire survey involving 115 respondents, selected using a snowball sampling method. The data were analyzed using multiple linear regression and Structural Equation Modeling Partial Least Squares (SEM-PLS). Findings – The results show that a positive work attitude significantly influences job satisfaction. In turn, higher job satisfaction is found to reduce the intention to change jobs. These findings provide a deeper understanding of the relationships between work attitude, job satisfaction, and job-switching intention within the context of freelance fashion models. Originality – This study highlights a relatively underexplored labor segment, freelance fashion models, who face unique employment challenges in a largely informal industry. It provides empirical insights into psychological and organizational factors affecting their work engagement and retention.